Promoting and preserving safe and active mobility in Istanbul during the COVID-19 pandemic. (20th October 2021) - Demir, O; Rojhani, A; Hung, C
Abstract: The COVID-19 pandemic severely impacted all facets of daily life, including and especially mobility within urban centres. As part of efforts to control the virus by encouraging citizens to stay at home, local governments imposed public health and social measures (PHSMs) restricting the availability and use of public transit. The result was an immediate, sharp decline in the use of public transit, and later as the pandemic was brought under control in certain geographies, a reluctance to return to using public transportation due to sustained fears of virus transmission. In Istanbul, Turkey, the use of public transportation decreased by over 90%, coupled with a significant rise in the use of private motorised transportation. To counter this trend, the Istanbul Metropolitan Municipality (IMM) joined cities around the world in implementing a two-pronged strategy to support safe and active mobility during the pandemic. IMM first launched a communication campaign to promote adherence to PHSMs, to rebuild trust in the safety of public transportation as restrictions eased, and to educate citizens on transportation alternatives. Billboards, social media and digital screens on public transportation promoted continued mask use, hand-washing and physical distancing and encouraged citizens wary of returning to public transit to consider walking or cycling as a safe and healthy alternative to private car use. IMM simultaneously enhanced their cycling infrastructure, creating new temporary and permanent bike lanes that closed connectivity gaps within the city. This talk will further elaborate on IMM's actions and the results and explore how they and other cities can sustain the focus on safe and active mobility as a longer-term strategy to reduce private car use and improve health outcomes.